ANALISIS BANTUAN KEUANGAN PROVINSI JAWA TENGAH KEPADA PEMERINTAH DESA UNTUK PENINGKATAN KETAHANAN MASYARAKAT DESA (PKMD) DI KABUPATEN KARANGANYAR TAHUN 2020 - Prihanto, Dwi (JI@P, 2021)
The purpose of this study is to determine the effectiveness of the assistance in Improving the Village Community Resilience (PKMD) of 2020. The policy of using Financial Assistance for the Village Governments for PKMD activities in 2020 was directed at the capital participation of BUMDesa to develop a village-food-business unit as a provider of basic food-necessity for the community. The method used is descriptive qualitative by using management actuating principles from Terry & Leslie in the implementation process. While to see its effectiveness the researcher used the Kenneth Boulding system schema approach with input-process-output. The data collection technique used is interviews and documentation. The implementation of the financial assistance for PKMD in Karanganyar Regency has been implemented properly according to the regulations. From the input indicator to the actualization which becomes the benchmark of the research, the actualization of this financial assistance has not met the maximum results yet, especially in the purpose of assistance, meeting the needs of cheap basic-necessities for the village residents affected by Covid. Because, in the distribution process, there are no strict rules from the village about who is allowed to buy cheap basic-necessities, everything is being entrusted to the village stalls as sales-partners of Bumdesa.